Two New Fumarprotocetraric Acid Lactones Identified and Characterized by UHPLC-PDA/ESI/ORBITRAP/MS/MS from the Antarctic Lichen Cladonia metacorallifera - Beatriz Sepúlveda; Alberto Cornejo; Daniela Bárcenas-Pérez; José Cheel; Carlos Areche (Separations, 2022)
Lichens are symbiotic organisms between algae and fungi, which are makers of secondary compounds named as lichen substances. Hyphenated techniques have significantly helped natural product chemistry, especially UHPLC/ESI/MS/MS in the identification, separation, and tentative characterization of secondary metabolites from natural sources. Twenty-five compounds were detected from the Antarctic lichen Cladonia metacorallifera for the first time using UHPLC-PDA/ESI/Orbitrap/MS/MS. Compounds 5 and 7 are reported as new compounds, based on their MS/MS fragmentation routes, and considered as fumarprotocetraric acid derivatives. Besides, ten known phenolic identified as orsellinic acid, ethyl 4-carboxyorsellinate, psoromic acid isomer, succinprotocetraric acid, siphulellic acid, connorstictic acid, cryptostictic acid, lecanoric acid, lobaric acid and gyrophoric acid are noticed for the first time in the Cladonia genus.